Modern weapons and military equipment for issue 3-2019 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2019)
Russia Has Tested Its Tsirkon Hypersonic Missile "Over Ten Test Launches"; Russian Forces are Adding a Silent-but-Deadly New Weapon to Their Arsenal; This Submarine Is "Invincible": Meet the Super Sub Headed to China's Doorstep; Russia Is Arming Its Tanks with a Controversial New 'Bullet'; Taiwan Sky Sword II; US Army adapts military-grade steel alloy for 3D printing ultra-strong parts; China’s 85,000 Ton Type 002 Carrier Will Be a High Tech EMALS Equipped Peer to America’s Gerald Ford Class